The Relationship Between Stroke Classification And Motor Function Impairment - Rafiqah Ramdania Ridwan; Achmad Harun; Emy Wardhani (Sean Institute, 2024)
Stroke is a sudden abnormality in brain function caused by problems with cerebral blood circulation. In the world, stroke is the second leading cause of death. There are two types of stroke: hemorrhagic and ischemic. Hemiplegia and hemiparesis are the most common motor disorders in patients who have had a stroke. This study investigates whether there is a relationship between stroke classification and impaired motor function experienced by patients who have had a stroke. This research used a literature review method by tracing the results of scientific publications in the time period between 2017 and 2024. From the results it was found that there was a significant relationship between motor function disorders and stroke classification.